International Liquidity and the Role of the SDR in the International Monetary System - Polak, J. (IMF Working Papers; Working Paper ;, 2002)
This paper describes how the changed conditions in the international monetary system have undermined the role originally envisaged for the SDR. It argues that the concept of a global stock of international liquidity, which was fundamental to the creation of the SDR, is now no longer relevant. Nonetheless, there are good reasons to satisfy part of the growing demand for international reserves with SDR allocations: (i) there are efficiency gains, as SDRs can be created at zero resource cost, and thus obviate the need for countries to run current account surpluses or engage in expensive borrowing to obtain reserves, and (ii) there would be a reduction in systemic risk, as SDRs would substitute to some extent for borrowed reserves, which are less reliable and predictable source of reserves, especially in times of crisis.